Identification of the protonation and oxidation states of the oxygen-evolving complex in the low-dose X-ray crystal structure of photosystem II - Saito, Keisuke; Nakao, Shu; Ishikita, Hiroshi (Frontiers in Plant Science, 2023)
The photosynthetic protein complex, photosystem II (PSII), comprises two identical monomers, namely A and B, both of which have identical oxygen-evolving complexes (Mn4CaO5 clusters). The oxygen atoms O3 and O4 in the Mn4CaO5 cluster are hydrogen-bonded to D1-His337 and an adjacent water molecule (W539), respectively. A low-dose X-ray analysis reported different structures of the Mn4CaO5 cluster between the two monomers in the PSII crystal [Tanaka et al., J. Am Chem. Soc. 2017, 139, 1718]. Using quantum mechanical/molecular mechanical approaches, we investigate hydrogen-bond distances between O3 and D1-His337 and between O4 and W539, which were found to be the main structural differences between monomers A and B. When O4 is protonated at the S1 state, the short O4-OW539 distance (< 2.5 Å) experimentally observed in the B monomer is reproduced. The short O3-N-His337 distance observed in the A monomer indicates the presence of a low-barrier hydrogen-bond that is involved in proton transfer between doubly-protonated D1-His337 and O3 in the over-reduced state (S−1 or S−2). These results suggest that the two Mn4CaO5 clusters in the PSII crystal have distinct oxidation states of S−1 or S−2 in the A monomer and S1 in the B monomer. Compared with the B monomer, the A monomer may easily be over-reduced due to X-ray radiation damage in the crystal.